Irradiation Embrittlement of WWER RPV Steels Irradiated at High Fluences (Journal of Nuclear Technology in Applied Science, 2020)
A statistical analysis of data obtained during impact testing of surveillance specimen of 15 WWER-440 RPVs operating in Russia, Ukraine, Armenia, Hungary, the Czech Republic and Slovakia was performed. The raw data used were selected from the IAEA International Database. As a result of the analysis, the influence of P and Cu to Tk increase was observed at a fluence up to 5 x 10^20 cm^-2 (E > 0.5 MeV), more than double design end of life WWER-440 fluence value. A proposal to increase the application range of normative dependences ΔTk(F) on reactor pressure vessel from 3 x 10^20 cm^-2 to 5 x 10^20 cm^-2 has been prepared to amend the regulatory and technical documents regarding the adjustment of the residual life of WWER-440 RPVs. It will allow the WWER-440 RPV to be operated for 60-80 years without annealing the base metal and in some cases without annealing the irradiated welds.
Keywords: reactor pressure vessel; neutron fluence; irradiation embrittlement